Attitudes of Physicians and Nurses toward family presence during resuscitation in emergency rooms of hospitals affiliated with Tehran, Iran and Shahid Beheshti Universities of Medical Sciences - Dabiriyan, A; Malek Hoseini, Sh; Ashk-e-torab, T; Alavi Majd, H; Ezati, Zh (Advances in Nursing & Midwifery, 2010)
Background and Aim Access to the resuscitation environment depends on attitudes of staff of emergency rooms (ERs). Attitudes of health personnel differ to let family witness cardiopulmonary resuscitation. The aim of this study was conducted to determine physicians' and nurses' attitudes toward witnessing resuscitation by family in the ERs of hospitals affiliated with Tehran, Iran and Shahid Beheshti Universities of Medical Sciences & Health Services. Materials and methods This research was a descriptive study. 120 nurses by quota sampling method and all 60 physicians in emergency rooms of the hospitals were selected. Data were collected over two months by a questionnaire in 2 parts including 13 items for demographics and 31 questions for the attitude. Content and test-retest methods were used for validity and reliability (r=0.78) of the tool respectively. Findings 60% of the subjects were male, 55% had work experience between 1and 5, 43.9% was single and 83.9% was between 25 and 35. 70% of the physicians and 91.7% of nurses had previous reading regarding the presence of a family member during resuscitation. 53.3% of the physicians and 56.7% of the nurses had no tendency to let a family member stay in the ER during cardiopulmonary resuscitation (CPR). No significant difference was found between the attitudes of physicians and nurses in this regard. 66.2% had no view in this respect. Conclusion One of the basic needs of clients and their family members is advocacy in critical situations and one of these situations for them is CPR. Clinical staff should provide the opportunity for the presence of a family member during CPR and support patients and their families. Keywords: Attitude, Physician, Nurse, Presence of a family member, Cardiopulmonary resuscitation *Corresponding Author: Azam Dabiriyan. Dept. of Community Health Nursing, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences & Health Services, Tehran, Iran E-mail: aazamdabirian@yahoo.com